Perspektif Teologia Sistematik untuk Tugas Pelayanan Pendidikan Teologi - Suranto S (Sekolah Tinggi Theologia Nazarene Indonesia, 2015)
This paper is a systematic theology design which is underlying the role of theological education. In this paper, the author put the Bible as the primary basis and it will be developed with the support of various books from Christian education authors. The experiences of more than twenty years of service in Bible College are also coloring this paper. Theological basis from various dimensions such as anthropology, Christology, Pneumatology, Ecclesiology and Eschatology is regarded as important as theological education for churches today. By this effort, theological education will step on the true basis and can carry out the duty of its call.